Geometallurgy – Fifteen Years of Developments in Codelco: Pedro Carrasco Contributions - J Beniscelli (The Australasian Institute of Mining and Metallurgy, 2011)
Some words to honour Pedro:Pedro was among the few persons with a very high level in geology modelling, resource and reserve estimation, geometallurgy development, sampling theory applications and a deep understanding of the mining industry needs. He had brilliant ideas about new developments on economic geology. He was always looking at the long-term and proposed challenging questions a decade in advance on their solution.The fundamental aim of geometallurgy is to add economic value to the mining of mine resources by timely providing information and knowledge about the relevant metallurgical variables represented by their space models. In this manner, geometallurgy allows obtaining the optimal design of a project, mitigating processing risks, optimising and supporting production plans and identifying and assessing mining business opportunities.This paper describes the conceptual framework and geometallurgical definitions and some of Codelco’s experience during the last 15 years.